The rs9939609 polymorphism in the fat mass and obesity associated (FTO) gene is associated with obesity in Tunisian population. (17th November 2018) - Ben Halima, Meriam; Kallel, Amani; Baara, Abir; Ben Wafi, Safa; Sanhagi, Haifa; Slimane, Hedia; Jemaa, Riadh; Feki, Moncef
Abstract: Context: Variations in the fat mass and obesity-associated gene ( FTO ) has been associated with obesity in many populations, but the results are conflicting. Objective: The aim of this study was to evaluate the effect of the rs9939609 polymorphism in the FTO gene on obesity risk and plasma leptin, adiponectin, insulin and lipid concentrations in Tunisians. Materials and methods: Four hundred and ninety-four subjects with obesity and 334 non-obese participated in this study. The rs9939609 (T/A) genotype was determined by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. Results: Significant differences in genotype frequencies were observed between cases and controls. In the separate analysis by gender, the association between the AA genotype and obesity was statistically significant in women but not in men. After stratification by obesity class this association remains only with obesity class III. Discussion: Our study is in agreement with studies on Caucasian, Portuguese and Cebu Filipino populations where a gender-specific association was found between rs9939609 polymorphism and obesity. It is also in agreement with studies on Mexican, Spanish and European populations, where an association was found with obesity class III. Conclusion: The rs9939609 polymorphism of FTO gene is associated with obesity, especially obesity class III in women.